Financial Toxicity During Breast Cancer Treatment: A Qualitative Analysis to Inform Strategies for Mitigation. Issue 10 (October 2021) - Gharzai, Laila A.; Ryan, Kerry A.; Szczygiel, Lauren; Goold, Susan; Smith, Grace; Hawley, Sarah; Pottow, John; Jagsi, Reshma
Abstract : PURPOSE: Financial toxicity from cancer treatment is a growing concern. Its impact on patients requires refining our understanding of this phenomenon. We sought to characterize patients' experiences of financial toxicity in the context of an established framework to identify knowledge gaps and strategies for mitigation. METHODS: Semistructured interviews with patients with breast cancer who received financial aid from a philanthropic organization during treatment were conducted from February to May 2020. Interviews were transcribed and coded until thematic saturation was reached, and findings were contextualized within an existing financial toxicity framework. RESULTS: Thirty-two patients were interviewed, of whom 58% were non-Hispanic White. The mean age was 46 years. Diagnoses ranged from ductal carcinoma in situ to metastatic breast cancer. Concordant with an established framework, we found that direct and indirect costs determined objective financial burden and subjective financial distress stemmed from psychosocial, behavioral, and material impact of diagnosis and treatment. We identified expectations as a novel theme affecting financial toxicity. We identified knowledge gaps in treatment expectations, provider conversations, identification of resources, and support-finding and offer strategies for mitigating financial toxicity on the basis of participant responses, such as leveraging support from decision aids and allied providers. CONCLUSION: This qualitative study confirms an existing framework for understanding financial toxicity and identifies treatment expectations as a novel theme affecting both objective financial burden and subjective financial distress. Four knowledge gaps are identified, and strategies for mitigating financial toxicity are offered. Mitigating patients' financial toxicity is an important unmet need in optimizing cancer treatment.